UTILIZING THE HEALTH BELIEF MODEL TO OPTIMIZE PATIENT EDUCATION WITHIN FSPRx - Siddiqi, Imaan Asim (My University, 2024)
Purpose of Study The purpose of this project is to evaluate the effectiveness of HBM guided education on the health behaviors of individuals diagnosed with diabetes in rural North Carolina. Specifically, there will be a focus on enhancing the current set of survey questions in order to make it all inclusive and comprehensive to further highlight aspects of the HBM. By doing this, the changes in perceived susceptibility, severity, benefits, and barriers (along with self efficacy and cues to action) can be accurately recorded. Methodology With the start of FSPRx’s nutrition program, there will be administration of the curated surveys. These survey results will be collected and recorded in order to note the initial status of participant’s health behavior/mindset. Following the conclusion of the necessary sessions, the same surveys will be utilized in order to record changes in said health behavior. The optimal result will be a significant increase in perception of all aspects of the HBM. Results The FSPRx’s nutrition/chronic disease portion will not be held until spring. As such, there is no definitive data to discuss or specific conclusions to draw at this time. The anticipated results will be gathered as a product of comparison between the surveys administered before and after this section of the program.
Keywords: Health Belief Model Patient Education Chronic Health Management